A discourse–design approach to multimodality: the visual communication of neoliberal management discourse. Issue 1 (1st January 2016) - Ledin, Per; Machin, David
ABSTRACT: This paper takes a discourse–design approach to communication, providing a framework as to how this should be done. Design here is how individuals and institutions realize their interests in the world. We show how it is fruitful to link design more closely to the way discourse has been used in critical studies which draws attention to the motivated use of design, for thinking about design in terms of socio-political context. Due to their affordances, semiotic modes such as photography, graphics, layout, colour, numbers and writing will be deployed and co-articulated. The aim, using a discourse–design approach, is to show how we can best identify the very different affordances of such modes and how they rely on the principled design of a discourse. We illustrate this using examples from management documents at a university which draw on these different affordances in different ways to communicate the same discourse. Through this analysis we see how a neoliberal discourse based on a general design principle of coordination enters everyday practices and become very difficult to challenge.